Komunikowanie przekazu w modelach stosunków prawnych (na przykładzie przepisów „ Kodeksu pracy ”) - Lizisowa, Maria Teresa (Stylistyka, 2021)
The present paper presents a discursive interpretation of legał regulations, understood as a particular delineation of communication between a legislator and the receivers of normative statements. The author shows, that the way of communicating a statement in an interacting community, artificially created by a law, is schematic and happens according to two patterns. While regulating the actions of legał subjects in relations conceming legał obligations, a legislator refers writs to the receivers of normative statements. The writs take a form of categorical statements, composed of indicative sentences as well as they specify the time of establishing and receiving of the act of speech, in deictic temporal setting around a pivot of “here and now”, given by a legislature. In the case of combining legał obligations and interactions of dependence of authority, a statement determining the way of solving a dispute between the subjects of legał obligations (e.g. between an em- ployer and an employee), through subjects of authority (e.g. employment courts), is given in the form of conditional sentences. Temporal setting of events in the statements regulating interactions of dependence of authority, determines projection on the time pivot. Ac- cording to the author, the syntactic organisation of sentences and the temporality alloca- ted as the duration of actions suspended in time are the main grammatical ąualities of the functional marking of legał texts.